The epidemiology of contact allergy in the general population - prevalence and main findings - Thyssen, Jacob Pontoppidan; Linneberg, Allan; Menné, Torkil; Johansen, Jeanne Duus (Contact dermatitis, 2007)
A substantial number of studies have investigated the prevalence of contact allergy in the general population and in unselected subgroups of the general population. The aim of this review was to determine a median prevalence and summarize the main findings from studies on contact allergy in the general population. Published research mainly originates from North America and Western Europe. The median prevalence of contact allergy to at least 1 allergen was 21.2% (range 12.5–40.6%), and the weighted average prevalence was 19.5%, based on data collected on all age groups and all countries between 1966 and 2007. The most prevalent contact allergens were nickel, thimerosal, and fragrance mix. The median nickel allergy prevalence was 8.6% (range 0.7–27.8%) and demonstrates that nickel was an important cause of contact allergy in the general population and that it was widespread in both men and women. Numerous studies demonstrated that pierced ears were a significant risk factor for nickel allergy. Nickel was a risk factor for hand eczema in women. Finally, heavy smoking was associated with contact allergy, mostly in women. Population‐based epidemiological studies are considered a prerequisite in the surveillance of national and international contact allergy epidemics.